Titania–Graphene Oxide Nanocomposite-Based Philadelphia-Positive Leukemia Therapy - Batool, Maria; Qazi, Rida-e-Maria; Mudassir, Muhammad Ahmad; Sajid, Zahra; Zaman, Rena; Rauf, Mhd Ahmar; Kousar, Shazia; Ahmad, Israr; Rehman, Fawad Ur; Mian, Afsar Ali (ACS applied bio materials, 2024)
Philadelphia-positive (Ph+) leukemia is a type of blood cancer also known as acute lymphoblastic leukemia (ALL), affecting 20–30% of adults diagnosed worldwide and having an engraved prognosis as compared to other types of leukemia. The current treatment regimens mainly rely on tyrosine kinase inhibitors (TKIs) and bone marrow transplants. To date, several generations of TKIs have been developed due to associated resistance and frequent relapse, with cardiovascular system anomalies being the most devastating complication. Nanotechnology has the potential to address these limitations by the targeted drug delivery and controlled release of TKIs. This study focused on the titanium dioxide (TiO2) and graphene oxide (GO) nanocomposite employment to load nilotinib and ponatinib TKIs for therapy of Ph+ leukemia cell line (K562) and Ba/F3 cells engineered to express BCR-ABL oncogene. Meanwhile, after treatment, the oncogene expressing fibroblast cells (Rat-1 P185) were evaluated for their colony formation ability under 3D conditions. To validate the nanocomposite formation, the TiO2–GO nanocomposites were characterized by scanning electron microscope, DLS, XRD, FTIR, zeta potential, EDX, and element mapping. The TKI-loaded TiO2–GO was not inferior to the free drugs after evaluating their effects by a cell viability assay (XTT), apoptosis induction, and colony formation inhibition. The cell signaling pathways of the mammalian target of rapamycin (mTOR), signal transducers and activators of transcription 5 (STAT5), and extracellular signal-regulated kinase (Erk1/2) were also investigated by Western blot. These signaling pathways were significantly downregulated in the TKI-loaded TiO2–GO-treated groups. Based on the findings above, we can conclude that TiO2–GO exhibited excellent drug delivery potential that can be used for Ph+ leukemia therapy in the future, subject to further investigations.